Estudio de prefactibilidad para la Instalación de una heladería especializada en la elaboración de helados congelados con nitrógeno líquido - Becerra Giha, Micaela Maria (2020)
The following prefeasibility study will determine the feasibility of implementing a specialized ice cream facility base on a liquid nitrogen freezing process in Lima Metropolitana. For this, the research problem was evaluated, establishing the objectives, and the scope. The subject was justified and the hypotheses were presented. Different theses found in the library of the University of Lima were used as references. It was necessary to implement a market research in order to determine the demand and interest from the target audience, therefor surveys were carried out. Based on the surveys and diferente relevant factors of the study such as proximity to the target audience, polarization, security and others, the location of the ice cream facility was determined. The size of the business was also determined analyzing factors such as market, resources, investment, etc. An analysis of all the activities and processes that will be carried out in the facilities for the proper functioning of the service was performed. Having this analysis, the personnel that would be in charge of each of the activities and their specific functions were determined. A compilation of all the income and expenses that the business would have was made in order to perform a financial evaluation of the service.